Metabolic alterations in meningioma reflect the clinical course - Masalha, Waseem; Daka, Karam; Woerner, Jakob; Pompe, Nils; Weber, Stefan; Delev, Daniel; Krüger, Marie T.; Schnell, Oliver; Beck, Jürgen; Heiland, Dieter Henrik; Grauvogel, Juergen (BMC Cancer, 2021)
Background: Meningiomas are common brain tumours that are usually defined by benign clinical course. However, some meningiomas undergo a malignant transformation and recur within a short time period regardless of their World Health Organization (WHO) grade. The current study aimed to identify potential markers that can discriminate between benign and malignant meningioma courses. Methods: We profiled the metabolites from 43 patients with low- and high-grade meningiomas. Tumour specimens were analyzed by nuclear magnetic resonance analysis; 270 metabolites were identified and clustered with the AutoPipe algorithm. Results: We observed two distinct clusters marked by alterations in glycine/serine and choline/tryptophan metabolism. Glycine/serine cluster showed significantly lower WHO grades and proliferation rates. Also progression-free survival was significantly longer in the glycine/serine cluster. Conclusion: Our findings suggest that alterations in glycine/serine metabolism are associated with lower proliferation and more recurrent tumours. Altered choline/tryptophan metabolism was associated with increases proliferation, and recurrence. Our results suggest that tumour malignancy can be reflected by metabolic alterations, which may support histological classifications to predict the clinical outcome of patients with meningiomas.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Meningioma; Tumour metabolism